Effect of pH variation on the subcritical crack growth parameters of glassy matrix ceramics - Melo, Renata M. [UNESP]; Pereira, Cristiane [UNESP]; Ramos, Nathália C. [UNESP]; Feitosa, Fernanda A. [UNESP]; Dal Piva, Amanda M.O. [UNESP]; Tribst, João Paulo M. [UNESP]; Özcan, Multu; Jorge, Antonio O.C. [UNESP] (Wiley, 2019)
The goals of our study were to calculate the subcritical crack growth (SCG) parameters of two veneering ceramics stored in water or Streptococcus mutans (S. mutans) biofilm and remineralizing medium, with indentation flaws. Feldspar (VM7) and leucite-reinforced (VM13) glass ceramic disks (Vita Zahnfabrik, Bad Säckingen, Germany) were made according to ISO 6872. Some specimens were indented with a Vickers diamond and the crack dimensions were measured. The specimens were fractured for a calculation of inert strength or further stored in water or submitted to pH variation, under preloading tension. Finally, the SCG parameters were calculated after the specimens were fractured under four stressing rates (MPa/s). Weibull analysis was conducted on non-indented specimens. XPS was performed as qualitative analysis. The subcritical crack of leucite ceramic did not vary with the media storage, but the glass-ceramic experienced a retarded growth after pH variation. The materials presented low Weibull modulus. Qualitative elemental analyses showed chemical modification on both ceramics. Therefore, the crack growth of leucite-reinforced ceramic was less affected by the environment pH than glass-ceramic.
Keywords: aging; crack velocity; fatigue; glass-ceramics; subcritical crack growth